Effects of non-steroidal antiinflammatory drugs on the glycemic satae and inflammatory marker in poorly controlled type ii dm patients - Kathem H. Sarmed; Ismail K. Dawser; Ismail H. Sajida; Hussain I. Khalid; Hussain A. Saad (College of Pharmacy / Mustansiriyah University, 2006)
Recent studies have shown that inflammatory markers like C-reactive protein (CRP) predicts future risk of diabetes mellitus (DM), and the data about the relationship between inflammation and the role of cyclooxygenase (COX) enzyme with type 2 DM are scar. In the present study, the clinical use of COX-inhibitors to improve glycemic state in type 2, poorly controlled DM patients was tested. Thirty eight(38) type 2 diabetic patients (12 males and 26 females) with age range of 55±S.E.1.25yrs., who are maintained on hypoglycemic agents for 6.5±S.E.0.92 years, but with poor glycemic control, were included in the study and randomly allocated into 3 groups; first group was treated with 25mg/day rofecoxib and the second was treated with 100 mg/day diclofenac for 2 months. The third group served as control for comparison. Fasting serum glucose (FSG), glycated hemoglobin (HbA1c), CRP and body mass index (BMI) were evaluated pre- and post-treatment. All the poorly controlled type 2DM patients included in the study were presented with high CRP levels. Treatment with rofecoxib and diclofenac for 60 days, showed relatively non-significant decrease in CRP, and did not produce any significant improvement in glycemic control. It could be concluded that COX pathway may not be the major contributor to the inflammatory events associated with DM and its associated complications. Further extensive pharmacologically based evaluation in this respect was necessary.